Environment-friendly high-toughness high-low-temperature-resistant corrosion-resistant polyamide elastomer as well as preparation and application thereof

By using biphthalic acid monomers, naphthalene dicarboxylic acid monomers and other raw materials for one-step polycondensation reaction, high-performance environmentally friendly polyamide elastomers were prepared, which solved the problem of poor resistance to existing elastomers in highly corrosive environments, and achieved high strength, ultra-high toughness and high and low temperature resistance.

CN119638983AActive Publication Date: 2025-03-18SICHUAN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411951349.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-18
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The existing polyurethane type and polyester copolymerized elastomers have poor resistance in highly corrosive environments, low heat resistance, and are difficult to take into account both high strength and high elastic deformation, and their adhesion to the matrix material is limited.

Method used

Biphenyl monomer, naphthalene dicarboxylic acid monomer, aliphatic diamine, polyether amine, catalyst, blocking agent and water as raw materials were used to carry out polycondensation reaction in a one-step manner under the action of the catalyst to prepare a high-performance environmentally friendly polyamide elastomer with a new structure.

Benefits of technology

It achieves high strength, ultra-high toughness, high and low temperature resistance and corrosion resistance, while improving the bonding strength to the matrix material and adapting to a more demanding use environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638983A_ABST
    Figure CN119638983A_ABST
Patent Text Reader

Abstract

The invention relates to an environment-friendly high-toughness high-low-temperature-resistant corrosion-resistant polyamide elastomer as well as preparation and application thereof, and belongs to the field of polymer synthesis. The invention provides a polyamide elastomer. The structural formula of the polyamide elastomer is as shown in formula I in the specification. The environment-friendly, high-toughness, high-temperature-resistant and corrosion-resistant elastomer with a new structure is prepared, and due to introduction of biphenyl and naphthalene ring structures, the resin is endowed with excellent heat and corrosion resistance and outstanding rigid and flexible mechanical properties (the tensile strength reaches about 80 MPa, and the elongation at break can reach 900%). # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an environmentally friendly, high-toughness, high-low temperature, corrosion-resistant polyamide elastomer and preparation and application thereof, belonging to the field of polymer synthesis. Background Art

[0002] Polyamide elastomers are widely used in aerospace oil-resistant sealing parts, electronic packaging, surface coatings, sports equipment such as sports shoes, sports equipment, infrastructure such as plastic tracks, etc. due to their excellent elasticity, deformation and mechanical properties; traditional elastomers mainly include polyurethane (PU) and polyester copolymers (TPE, TPA, etc.), both of which have good mechanical properties, elastic deformation, etc., but because their molecular chains contain ester bonds, their tolerance in highly corrosive environments is poor, and their heat resistance is not high. Generally, the long-term use temperature is less than 130°C, and it is difficult to take into account high strength and high elastic deformation at the same time; in addition, when used as a coating material, its adhesion and adhesion to the base material are limited and need to be further improved. Summary of the invention

[0003] The purpose of the present invention is to provide an environmentally friendly, high-strength, high-toughness, high-temperature and corrosion-resistant polyamide elastomer in view of the deficiencies in the prior art. The elastomer is characterized in that biphenyl dicarboxylic acid monomer, naphthalene dicarboxylic acid monomer, aliphatic diamine, polyether amine, catalyst, end-capping agent, water, etc. are used as raw materials, and a condensation reaction is carried out in a one-step process under the action of a catalyst to prepare a high-performance, environmentally friendly, high-strength, high-toughness, high-temperature and corrosion-resistant body with a new structure.

[0004] The technical solution of the present invention:

[0005] The first technical problem to be solved by the present invention is to provide an environmentally friendly, high-toughness, high-temperature, corrosion-resistant polyamide elastomer, the structural formula of which is shown in Formula I:

[0006]

[0007] in,

[0008] At least one of;

[0009] At least one of;

[0010]

[0011] Any one of the following; 20≤n≤300.

[0012] Furthermore, the environmentally friendly, high-toughness, high-temperature-resistant and corrosion-resistant polyamide elastomer is selected from one of the substances represented by the following structural formula:

[0013] Furthermore, the environmentally friendly, high-strength, high-toughness, high-temperature, corrosion-resistant polyamide elastomer has a tensile strength of 39 to 87 MPa, an elongation at break of 800 to 1050%, and a Vicat softening point of 114 to 151°C; that is, the elastomer obtained by the present invention has the characteristics of high and low temperature resistance, high strength, ultra-high toughness and high bonding strength.

[0014] The second technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned environmentally friendly, high-toughness, high-temperature, and corrosion-resistant polyamide elastomer, wherein the preparation method comprises preparing the polyamide elastomer by a one-step polycondensation reaction of the raw materials under the action of a catalyst;

[0015] The raw materials include: biphenyl dicarboxylic acid monomer, naphthalene dicarboxylic acid monomer, aliphatic diamine, polyether amine, catalyst, end-capping agent or water; the proportion of each raw material is:

[0016]

[0017]

[0018] Further, the biphenyl dicarboxylic acid monomer is

[0019] At least one of;

[0020] The naphthalene dicarboxylic acid monomer is

[0021] At least one of;

[0022] The aliphatic diamine is selected from:

[0023]

[0024] Any of;

[0025] The polyetheramine is selected from:

[0026]

[0027] Any of .

[0028] Further, the end-capping agent is:

[0029]

[0030] Any of .

[0031] Furthermore, the catalyst is selected from the group consisting of triphenyl phosphite, phosphorous acid, sodium hypophosphite, sodium phosphite, trimethylchlorosilane, triethylsilyl chloride, tin chloride, stannous octoate, heteropolyacid chromium monophosphate (C 52 H 119 CrMo6N4O24 ), heteropolyacid unilateral iron (C 52 H 119 FeMo6N4O 24 ), heteropoly acid unilateral manganese (C 52 H 119 M n Mo6N4O 24 ), heteropolyacid unilateral aluminum (C 52 H 119 AlMo6N4O 24 ), N,N'-dicyclohexylcarbodiimide (DCC), benzotriazole-N,N,N',N'-tetramethyluronium hexafluorophosphate (HBTU) or 1-hydroxybenzotriazole (HOBT).

[0032] Furthermore, the preparation method of the above-mentioned environmentally friendly, high-toughness, high-temperature-resistant and corrosion-resistant polyamide elastomer comprises the following steps:

[0033] 24.2-121 parts of biphenyl dicarboxylic acid monomer, 108-194.4 parts of naphthalene dicarboxylic acid monomer, 30-208.8 parts of aliphatic diamine, 40-1000 parts of polyether amine, 0.1-40 parts of catalyst and 10-500 parts of deionized water are added to a reaction kettle respectively, and the mixture is heated to 50-100°C under a nitrogen atmosphere and stirred for reaction for 0.5-1h, and the pH value of the solution is controlled at 7.5-8.5; then, the reaction kettle is sealed and heated, and the temperature is raised to 210-230°C in the first stage, and the reaction is carried out for 1-3h; the temperature is then raised to 231-250°C, and the reaction is carried out for 1-3h, and exhaust is performed in the middle. 1 to 3 times; then heat the reactor to 251 to 280°C, maintain the vacuum degree at -0.08 to -0.095 MPa, continue the reaction for 2 to 6 hours, and use negative pressure to suck 0.1 to 20 parts of the end-capping agent into the reactor, and continue the reaction for 0.5 to 2 hours, stop the polymerization reaction, introduce nitrogen into the reactor until it returns to normal pressure, open the reactor discharge bottom valve, and continue to use 0.02-0.1 MPa nitrogen to extrude the material in the reactor from the discharge valve to the feed port of the twin-screw extruder, and vent, extrude, pelletize and dry to obtain an environmentally friendly, high-strength, high-temperature, corrosion-resistant polyamide elastomer resin.

[0034] Further, in the above preparation method, the process conditions of the twin-screw extruder are as follows:

[0035] The screw speed is controlled to be 80-300rpm, the feeding rate is 3-40, and the temperature of each section of the extruder is: section 1 (feeding port): 220-260°C, section 2: 220-260°C, section 3: 220-260°C, section 4: 220-260°C, section 5: 271-290°C, section 6: 271-290°C, section 7: 271-290°C, section 8: 271-290°C, section 9: 271-290°C, section 10: 271-290°C, section 11: 271-290°C, section 12: 271-290°C, section 13: 271-290°C, section 14 (die): 280-290°C.

[0036] In the present invention, the parts of raw materials are all parts by weight unless otherwise specified.

[0037] The third technical problem to be solved by the present invention is to point out that the above-mentioned environmentally friendly, high-strength, high-toughness, high-low-temperature-resistant and corrosion-resistant polyamide elastomer is used as a compatibilizer, an active additive, a soft plastic or a coating material.

[0038] Furthermore, the environmentally friendly, high-toughness, high-temperature-resistant and corrosion-resistant polyamide elastomer is used as an interface compatibilizer between inert resins such as fluororesins and metals such as aluminum sheets / titanium sheets / stainless steel.

[0039] Furthermore, the environmentally friendly, high-strength, high-toughness, high-low-temperature-resistant, and corrosion-resistant polyamide elastomer is used as a high-impact active additive.

[0040] Furthermore, the environmentally friendly, high-strength, high-toughness, high-low-temperature-resistant, and corrosion-resistant polyamide elastomer is used as a protective coating, etc.

[0041] Beneficial effects of the present invention:

[0042] 1. The present invention produces an environmentally friendly, high-strength, high-temperature and corrosion-resistant elastomer with a new structure. Due to the introduction of biphenyl and naphthalene ring structures, the resin is endowed with excellent heat and corrosion resistance and outstanding rigidity and flexibility mechanical properties (tensile strength reaches nearly 80MPa, and its elongation at break can reach 900%).

[0043] 2. Water is used as a solvent in the synthesis process of the present invention, which is green and pollution-free; in addition, a one-pot method is used for polymerization, which has a short process, a simple process and good stability.

[0044] 3. The reaction of the present invention is carried out in two stages. Compared with the traditional technical method, the end group of the product can be controlled more effectively. The use of the end group containing the tertiary amine structure can avoid the problems of active amino and carboxyl groups being easily oxidized and degraded during the processing. At the same time, due to the introduction of the positively charged tertiary amine end group, the resin is endowed with good bonding properties, which is beneficial to the subsequent bonding between the interface and the inert material.

[0045] 4. In the present invention, after the polymerization is completed, a reaction kettle is combined with a twin-screw extrusion pelletizing process to make the entire process completely continuous, while saving the energy consumption of secondary melting, which is more low-carbon.

[0046] 5. Compared with traditional elastomers, the elasticity obtained by the present invention has better high and low temperature performance, corrosion resistance, mechanical properties and bonding properties, and can adapt to more demanding use environments. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 These are the infrared test results of the elastomers obtained in Examples 1 to 6 of the present invention.

[0048] Figure 2 The mechanical property test results (stress-strain curve and tensile strength) of the elastomers obtained in Examples 1 to 6 of the present invention are shown.

[0049] Figure 3 These are the Vicat softening point test results of the elastomers obtained in Examples 1 to 6 of the present invention. DETAILED DESCRIPTION

[0050] The present invention adopts an electrophilic substitution route, uses biphenyl dicarboxylic acid, naphthalene dicarboxylic acid monomers and aliphatic diamine and polyether amine monomers for co-condensation, and obtains a polyamide type elastomer with a novel structure of different chain segment primitives. The molecular chain structure can be adjusted in a wide range (various diacid monomers and diamine monomers with different structures can be used for copolymerization), and its use temperature can be greatly optimized. Since there is no ester structure in the entire molecular chain segment and the rigid structures such as biphenyl and naphthalene ring exist, its corrosion resistance is relatively greatly improved. At the same time, the high-density amide structure greatly improves its mechanical properties. In addition, the tertiary amine structure also gives the resin excellent interface bonding performance.

[0051] The present invention is described in detail below through examples. It is necessary to point out that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make some non-essential improvements and adjustments based on the above contents of the present invention.

[0052] Example 1 (biphenyl diacid-10-naphthalene diacid-90-C14-80%-400-20%)

[0053] 24.2 g of 4,4'-biphenyl dicarboxylic acid monomer, 194.4 g of 1,4-naphthalene dicarboxylic acid monomer, 182.4 g of 1,14-tetradecane diamine, polyetheramine-400 80g, 0.1g of heteropolyacid unilateral manganese and 100g of deionized water were added to the reactor respectively, and the temperature was raised to 50°C under a nitrogen atmosphere for stirring and reacting for 0.5h, and the pH value of the solution was controlled to 7.5; then, the reactor was closed and heated, and the temperature was raised to 210°C in the first stage for reaction for 1h; then the temperature was raised to 231°C for reaction for 1h, and the exhaust was performed once in the middle; then the reactor was heated to 251°C, the vacuum degree was maintained at -0.08MPa, the reaction was continued for 2h, and 0.1g of the end-capping agent N,N-dimethylethylenediamine was sucked into the reactor by negative pressure, and the reaction was continued for 0.5h, the polymerization reaction was stopped, nitrogen was introduced into the reactor until it returned to normal pressure, and the bottom valve of the reactor was opened. , continue to use 0.02MPa nitrogen to extrude the material in the kettle from the discharge valves to the feed port of the twin-screw extruder, control the screw speed to 80rpm, the feeding rate to 3, the temperature of each section of the extruder: section 1 (feeding port): 220℃, section 2: 230℃, section 3: 230℃, section 4: 240℃, section 5: 271℃, section 6: 280℃, section 7: 280℃, section 8: 290℃, section 9: 290℃, section 10: 290℃, section 11: 290℃, section 12: 290℃, section 13: 290℃, section 14 (die): 280℃, and exhaust, extrude, pelletize and dry to obtain an environmentally friendly, high-strength, tough, high-temperature, and corrosion-resistant polyamide elastomer resin.

[0054] For infrared characterization, see Figure 1 As shown in the figure, the mechanical properties and Vicat softening point (the standard impact specimen is placed in a silicone oil bath, under a load of 1.82MPa and a temperature increase of 2℃ / min, the specimen is 1mm thick. 2 The temperature when the needle is pressed into 1mm) Figure 2-3 As shown: the tensile strength is 39.5MPa, the elongation at break is 882.3%, the Vicat softening point is 131.8℃, and the corrosion resistance experiment is shown in Table 1: it has excellent tolerance in traditional alkanes, alcohols, acetone, hydrochloric acid (1mol / L), and NaOH (1mol / L), and its corrosion resistance is greatly improved compared with traditional thermoplastic elastomers such as PU and TPE; it is applied to the interface compatibilizer of fluororesin and metal aluminum and titanium sheets, and its peel strength can reach 8.02N / cm and 8.24N / cm respectively.

[0055] Example 2 (biphenyl diacid-50-naphthalene diacid-50-C12-70%-1000-30%)

[0056] 108 g of 3,3'-biphenyl dicarboxylic acid monomer, 121 g of 2,6-naphthalene dicarboxylic acid monomer, 140 g of decanediamine, and polyetheramine-1000 300g, 1g of sodium phosphite and 500g of deionized water were added to the reactor respectively, and the temperature was raised to 60°C under a nitrogen atmosphere for stirring and reacting for 0.5h, and the pH value of the solution was controlled to 7.5; then, the reactor was closed and heated, and the temperature was raised to 210°C in the first stage for reaction for 1h; then the temperature was raised to 231°C for reaction for 1h, and exhaust was performed once in the middle; then the reactor was heated to 251°C, the vacuum degree was maintained at -0.08MPa, the reaction was continued for 2h, and 3g of the end-capping agent N,N-dimethylethylenediamine was sucked into the reactor by negative pressure, and the reaction was continued for 0.5h, the polymerization reaction was stopped, nitrogen was introduced into the reactor until it returned to normal pressure, the reactor discharge bottom valve was opened, and then 0.02MPa nitrogen is then used to extrude the material in the kettle from the discharge valves to the feed port of the twin-screw extruder, the screw speed is controlled to be 80rpm, the feeding rate is 3, and the temperature of each section of the extruder is: section 1 (feed port): 220°C, section 2: 230°C, section 3: 230°C, section 4: 240°C, section 5: 271°C, section 6: 280°C, section 7: 280°C, section 8: 290°C, section 9: 290°C, section 10: 290°C, section 11: 290°C, section 12: 290°C, section 13: 290°C, section 14 (die): 280°C, and exhaust, extrusion, pelletizing and drying are performed to obtain an environmentally friendly, high-strength, high-toughness, high-temperature, and corrosion-resistant polyamide elastomer resin.

[0057] For infrared characterization, see Figure 1 As shown in the figure, the mechanical properties and Vicat softening point (the standard impact specimen is placed in a silicone oil bath, at 1.82MPa, 2℃ / min heating conditions, the specimen is 1mm 2 The temperature when the needle is pressed into 1mm) Figure 2-3 As shown: the tensile strength is 55.7MPa, the elongation at break is 958.6%, the Vicat softening point is 114.5℃, and the corrosion resistance experiment is shown in Table 1: it has excellent tolerance in traditional alkanes, alcohols, acetone, hydrochloric acid (1mol / L), and NaOH (1mol / L), and its corrosion resistance is greatly improved compared with traditional thermoplastic elastomers such as PU and TPE; it is applied to the interface compatibilizer of fluororesin and metal aluminum sheet and titanium sheet, and its peel strength can reach 8.91N / cm and 8.78N / cm respectively.

[0058] Example 3 (biphenyl diacid-40-naphthalene diacid-60-C10-60%-2000-40%)

[0059] 96.8 g of 3,3'-biphenyl dicarboxylic acid monomer, 129.6 g of 1,4-naphthalene dicarboxylic acid monomer, 103.2 g of decanediamine, polyetheramine-2000 800g, 3g N,N'-dicyclohexylcarbodiimide and 500g deionized water were added to the reactor respectively, and the temperature was raised to 70°C under nitrogen atmosphere for stirring and reacting for 1h, and the pH value of the solution was controlled to 8; then, the reactor was closed and heated, and the temperature was raised to 210°C in the first stage for reaction for 1h; then the temperature was raised to 231°C for reaction for 2h, and the exhaust was performed twice in the middle; then the reactor was heated to 260°C, the vacuum degree was maintained at -0.08MPa, the reaction was continued for 2h, and 5g of the end-capping agent N,N-dimethyl-p-phenylenediamine was sucked into the reactor by negative pressure, and the reaction was continued for 1h, the polymerization reaction was stopped, nitrogen was introduced into the reactor until it returned to normal pressure, and the bottom valve of the reactor was opened. Continue to use 0.06MPa nitrogen to extrude the material in the kettle from the discharge valves to the feed port of the twin-screw extruder, control the screw speed to 180rpm, the feeding rate to 5, the temperature of each section of the extruder: section 1 (feeding port): 220℃, section 2: 230℃, section 3: 230℃, section 4: 230℃, section 5: 271℃, section 6: 280℃, section 7: 280℃, section 8: 280℃, section 9: 290℃, section 10: 290℃, section 11: 290℃, section 12: 290℃, section 13: 290℃, section 14 (die): 290℃, and exhaust, extrude, pelletize and dry to obtain an environmentally friendly, high-strength, high-toughness, high-temperature, and corrosion-resistant polyamide elastomer resin.

[0060] For infrared characterization, see Figure 1 As shown in the figure, the mechanical properties and Vicat softening point (the standard impact specimen is placed in a silicone oil bath, at 1.82MPa, 2℃ / min heating conditions, the specimen is 1mm 2 The temperature when the needle is pressed into 1mm) Figure 2-3 As shown: the tensile strength is 62.3MPa, the elongation at break is 1032.8%, the Vicat softening point is 116.2℃, and the corrosion resistance experiment is shown in Table 1: it has excellent tolerance in traditional alkanes, alcohols, acetone, hydrochloric acid (1mol / L), and NaOH (1mol / L), and its corrosion resistance is greatly improved compared with traditional thermoplastic elastomers such as PU and TPE; it is applied to the interface compatibilizer of fluororesin and metal aluminum sheet and titanium sheet, and its peel strength can reach 9.12N / cm and 9.08N / cm respectively.

[0061] Example 4 (biphenyl diacid-30-naphthalene diacid-70-cyclohexanediamine-70%-1000-30%)

[0062] 72.6 g of 3,3'-biphenyl dicarboxylic acid monomer, 151.2 g of 2,6-naphthalene dicarboxylic acid monomer, 79.8 g of cyclohexanediamine, and polyetheramine-1000 were added. 300g, 5g of N,N'-dicyclohexylcarbodiimide and 450g of deionized water were added to the reactor respectively, and the temperature was raised to 80°C under a nitrogen atmosphere for stirring and reacting for 1h, and the pH value of the solution was controlled to 8; then, the reactor was closed and heated, and the temperature was raised to 210°C in the first stage for reaction for 1h; then the temperature was raised to 240°C for reaction for 2h, and the exhaust was performed twice in the middle; then the reactor was heated to 270°C, the vacuum degree was maintained at -0.09MPa, the reaction was continued for 4h, and 10g of the end-capping agent N,N-dimethylpropylenediamine was sucked into the reactor by negative pressure, and the reaction was continued for 1h, the polymerization reaction was stopped, nitrogen was introduced into the reactor until it returned to normal pressure, and the bottom valve of the reactor was opened. Continue to use 0.06MPa nitrogen to extrude the material in the kettle from the discharge valves to the feed port of the twin-screw extruder, control the screw speed to 190rpm, the feeding rate to 8, the temperature of each section of the extruder: section 1 (feeding port): 220℃, section 2: 220℃, section 3: 230℃, section 4: 230℃, section 5: 280℃, section 6: 280℃, section 7: 280℃, section 8: 280℃, section 9: 280℃, section 10: 290℃, section 11: 290℃, section 12: 290℃, section 13: 290℃, section 14 (die): 290℃, and exhaust, extrude, pelletize and dry to obtain an environmentally friendly, high-strength, high-toughness, high-temperature, and corrosion-resistant polyamide elastomer resin.

[0063] For infrared characterization, see Figure 1 As shown in the figure, the mechanical properties and Vicat softening point (the standard impact specimen is placed in a silicone oil bath, at 1.82MPa, 2℃ / min heating conditions, the specimen is 1mm 2 The temperature when the needle is pressed into 1mm) Figure 2-3 As shown: the tensile strength is 71.7MPa, the elongation at break is 979.5%, the Vicat softening point is 133.9℃, and the corrosion resistance experiment is shown in Table 1: it has excellent tolerance in traditional alkanes, alcohols, acetone, hydrochloric acid (1mol / L), and NaOH (1mol / L), and its corrosion resistance is greatly improved compared with traditional thermoplastic elastomers such as PU and TPE; it is applied to the interface compatibilizer of fluororesin and metal aluminum sheet and titanium sheet, and its peel strength can reach 9.03N / cm and 9.21N / cm respectively.

[0064] Example 5 (biphenyl diacid-40-naphthalene diacid-60-octanediamine-70%-1000-30%)

[0065] 96.8 g of 3,3'-biphenyl dicarboxylic acid monomer, 129.6 g of 2,6-naphthalene dicarboxylic acid monomer, 100.8 g of octanediamine, and polyetheramine-1000 were added. 300g, 15g of triethylsilyl chloride and 400g of deionized water were added to the reactor respectively, and the temperature was raised to 90°C under nitrogen atmosphere for stirring and reacting for 1h, and the pH value of the solution was controlled to be 8.5; then, the reactor was closed and heated, and the temperature was raised to 210°C in the first stage for reaction for 1h; then the temperature was raised to 250°C for reaction for 2h, and the exhaust was performed 3 times in the middle; then the reactor was heated to 280°C, the vacuum degree was maintained at -0.09MPa, the reaction was continued for 5h, and 11g of the end-capping agent N,N,N'-trimethylpropylenediamine was sucked into the reactor by negative pressure, and the reaction was continued for 1h, the polymerization reaction was stopped, nitrogen was introduced into the reactor until it returned to normal pressure, the bottom valve of the reactor discharge was opened, and the reaction was continued. 0.06MPa nitrogen is then used to extrude the material in the kettle from the discharge valves to the feed port of the twin-screw extruder, the screw speed is controlled to be 220rpm, the feeding rate is 12, and the temperature of each section of the extruder is: section 1 (feeding port): 220°C, section 2: 230°C, section 3: 240°C, section 4: 250°C, section 5: 275°C, section 6: 275°C, section 7: 280°C, section 8: 280°C, section 9: 280°C, section 10: 285°C, section 11: 285°C, section 12: 290°C, section 13: 290°C, section 14 (die): 290°C, and exhaust, extrusion, pelletizing and drying are performed to obtain an environmentally friendly, high-strength, high-toughness, high-temperature, and corrosion-resistant polyamide elastomer resin.

[0066] For infrared characterization, see Figure 1 As shown in the figure, the mechanical properties and Vicat softening point (the standard impact specimen is placed in a silicone oil bath, at 1.82MPa, 2℃ / min heating conditions, the specimen is 1mm 2 The temperature when the needle is pressed into 1mm) Figure 2-3 As shown: the tensile strength is 80.2MPa, the elongation at break is 951.9%, the Vicat softening point is 146.6℃, and the corrosion resistance experiment is shown in Table 1: it has excellent tolerance in traditional alkanes, alcohols, acetone, hydrochloric acid (1mol / L), and NaOH (1mol / L), and its corrosion resistance is greatly improved compared with traditional thermoplastic elastomers such as PU and TPE; it is applied to the interface compatibilizer of fluororesin and metal aluminum sheet and titanium sheet, and its peel strength can reach 9.46N / cm and 9.94N / cm respectively.

[0067] Example 6 (biphenyl diacid-40-naphthalene diacid-60-diaminodicyclohexyldimethylmethane-80%-400-30%)

[0068] 96.8 g of 4,4'-biphenyl dicarboxylic acid monomer, 129.6 g of 2,6-naphthalene dicarboxylic acid monomer, 185.6 g of diaminodicyclohexyl dimethyl methane, polyetheramine-400 120g, 35g of benzotriazole-N,N,N',N'-tetramethyluronium hexafluorophosphate (HBTU) and 320g of deionized water were added to the reactor respectively, and the temperature was raised to 85°C under a nitrogen atmosphere for stirring and reacting for 1h, and the pH value of the solution was controlled to be 8.3; then, the reactor was closed and heated, and the temperature was raised to 210°C in the first stage for reaction for 1h; then the temperature was raised to 245°C for reaction for 3h, and the exhaust was performed 3 times in the middle; then the reactor was heated to 275°C, the vacuum degree was maintained at -0.09MPa, the reaction was continued for 4.5h, and 20g of the end-capping agent N,N,N'-trimethylpropylenediamine was sucked into the reactor by negative pressure, and the reaction was continued for 1h, the polymerization reaction was stopped, and nitrogen was introduced into the reactor until it was restored to At normal pressure, open the discharge bottom valve of the reactor, continue to use 0.07MPa nitrogen to extrude the material in the reactor from the discharge valves to the feed port of the twin-screw extruder, control the screw speed to 240rpm, the feeding rate to 40, the temperature of each section of the extruder: section 1 (feeding port): 220℃, section 2: 230℃, section 3: 235℃, section 4: 245℃, section 5: 275℃, section 6: 275℃, section 7: 280℃, section 8: 280℃, section 9: 285℃, section 10: 285℃, section 11: 285℃, section 12: 290℃, section 13: 290℃, section 14 (die): 285℃, and exhaust, extrude, pelletize and dry to obtain an environmentally friendly, high-strength, high-toughness, high-temperature, and corrosion-resistant polyamide elastomer resin.

[0069] For infrared characterization, see Figure 1 As shown in the figure, the mechanical properties and Vicat softening point (the standard impact specimen is placed in a silicone oil bath, at 1.82MPa, 2℃ / min heating conditions, the specimen is 1mm 2 The temperature when the needle is pressed into 1mm) Figure 2-3 As shown in Table 1: the tensile strength is 86.3MPa, the elongation at break is 848.3%, the Vicat softening point is 150.7℃, and the corrosion resistance experiment is shown in Table 1: it has excellent tolerance in traditional alkanes, alcohols, acetone, hydrochloric acid (1mol / L), and NaOH (1mol / L), and its corrosion resistance is greatly improved compared with traditional thermoplastic elastomers such as PU and TPE; it is applied to the interface compatibilizer of fluororesin and metal aluminum sheet and titanium sheet, and its peel strength can reach 10.18N / cm and 9.80N / cm respectively.

[0070] Table 1 Corrosion resistance test of elastomers obtained in Examples 1-6

[0071]

[0072]

[0073] +-: Swelling, ++: Dissolved at room temperature, -: Insoluble

[0074] Comparative Example 1 (biphenyl diacid-10-naphthalene diacid-90-C14-80%-400-20%) without adding tertiary amine capping agent

[0075] 24.2 g of 4,4'-biphenyl dicarboxylic acid monomer, 194.4 g of 1,4-naphthalene dicarboxylic acid monomer, 182.4 g of tetradecanediamine, polyetheramine-400 80g, 0.1g of heteropolyacid unilateral manganese and 100g of deionized water were added to the reactor respectively, and the temperature was raised to 50°C under a nitrogen atmosphere for stirring and reacting for 0.5h, and the pH value of the solution was controlled to 7.5; then, the reactor was closed and heated, and the temperature was raised to 210°C in the first stage for reaction for 1h; then the temperature was raised to 231°C for reaction for 1h, and the exhaust was performed once in the middle; then the reactor was heated to 251°C, the vacuum degree was maintained at -0.08MPa, the reaction was continued for 2h, the polymerization reaction was stopped, nitrogen was introduced into the reactor until it returned to normal pressure, the bottom valve of the reactor discharge was opened, and 0.02MPa nitrogen was continued to be used to The material in the kettle is extruded from the discharge valves to the feeding port of the twin-screw extruder. The screw speed is controlled to be 80 rpm, the feeding rate is 3, and the temperature of each section of the extruder is: section 1 (feeding port): 220°C, section 2: 230°C, section 3: 230°C, section 4: 240°C, section 5: 271°C, section 6: 280°C, section 7: 280°C, section 8: 290°C, section 9: 290°C, section 10: 290°C, section 11: 290°C, section 12: 290°C, section 13: 290°C, section 14 (die): 280°C, and exhaust, extrusion, pelletizing and drying are carried out to obtain the polyamide elastomer resin.

[0076] The mechanical properties and Vicat softening points are:

[0077] Its tensile strength is 36.9MPa, elongation at break is 789.3%, and Vicat softening point (the standard impact specimen is placed in a silicone oil bath, at 1.82MPa, 2℃ / min heating conditions, the specimen is 1mm 2 The temperature when the needle is pressed into 1mm) is 130.0℃. The corrosion resistance experiment is shown in Table 1: it has similar tolerance to the resin obtained in Example 1 in traditional alkanes, alcohols, acetone, hydrochloric acid (1mol / L), and NaOH (1mol / L), but poor tolerance in alkaline solution. It is applied as an interface compatibilizer between fluororesin and metal aluminum and titanium sheets, and its peel strengths are only 2.46N / cm and 2.83N / cm, respectively.

[0078] Comparative Example 2 (biphenyl diacid-10-naphthalene diacid-90-C14-80%-PEG-800-20%)

[0079] 24.2 g of 4,4'-biphenyldicarboxylic acid monomer, 194.4 g of 1,4-naphthalene dicarboxylic acid monomer, 182.4 g of tetradecane diamine, 0.1 g of heteropolyacid unilateral manganese, and 100 g of deionized water were added to the reactor respectively, and the temperature was raised to 50°C under a nitrogen atmosphere for stirring and reacting for 0.5 h, and the pH value of the solution was controlled to be 7.5; then, the reactor was sealed and heated, and the temperature was raised to 210°C in the first stage for reaction for 1 h; then the temperature was raised to 231°C for reaction for 1 h, and the exhaust was performed once in the middle, and the reactor was evacuated to maintain a vacuum degree of -0.08 MPa, and then PEG-800 The mixture of 160g of PEG-800 and 1g of titanate was added to a closed feeding tank, heated to 80°C and melted evenly, then the valve between the feeding tank and the reactor was opened, PEG-800 and titanate catalyst were sucked into the reactor by negative pressure, and the feeding tank was purged with 0.1MPa nitrogen. After purging, all the connecting valves of the feeding tank were closed; then the reactor was heated to 251°C, the vacuum degree was maintained at -0.08MPa, the reaction was continued for 2h, the polymerization reaction was stopped, nitrogen was introduced into the reactor until it returned to normal pressure, the bottom valve of the reactor was opened, and the materials in the reactor were continued to be purged from the reactor with 0.02MPa nitrogen. The material is extruded to the feeding port of the twin-screw extruder through the discharge valves, the screw speed is controlled to be 80rpm, the feeding rate is 3, the temperature of each section of the extruder is: section 1 (feeding port): 220°C, section 2: 230°C, section 3: 230°C, section 4: 240°C, section 5: 271°C, section 6: 280°C, section 7: 280°C, section 8: 290°C, section 9: 290°C, section 10: 290°C, section 11: 290°C, section 12: 290°C, section 13: 290°C, section 14 (die): 280°C, and exhaust, extrusion, pelletizing and drying are carried out to obtain the polyamide elastomer resin.

[0080] The tensile strength of the obtained product is 35.3MPa, and the elongation at break is 762%. It degrades or even dissolves in strong acids and alkalis, and its mechanical properties drop sharply. In addition, when it is used as an interface compatibilizer between fluororesins such as polyperfluoroethylene propylene and aluminum and titanium sheets, its peel strength is only 2.2N / cm.

Claims

1. A polyamide elastomer, characterized in that: The structural formula of the polyamide elastomer is shown in Formula I: in, At least one of; At least one of; Any one of the following; 20≤n≤300.

2. A polyamide elastomer according to claim 1, characterized in that: The tensile strength of the polyamide elastomer is 39 to 87 MPa; or The elongation at break of the polyamide elastomer is 800-1050%; or: The Vicat softening point of the polyamide elastomer is 114-151°C.

3. The method for preparing a polyamide elastomer according to claim 1 or 2, characterized in that: The preparation method comprises the following steps: subjecting the raw materials to a one-step polycondensation reaction under the action of a catalyst to obtain the polyamide elastomer; The raw materials include: biphenyl dicarboxylic acid monomer, naphthalene dicarboxylic acid monomer, aliphatic diamine, polyether amine, catalyst, end-capping agent or water; the proportion of each raw material is:

4. The method for preparing a polyamide elastomer according to claim 3, characterized in that: The biphenyl dicarboxylic acid monomer is At least one; The naphthalene dicarboxylic acid monomer is At least one of; The aliphatic diamine is selected from: Any of; The polyetheramine is selected from: Any of .

5. The method for preparing a polyamide elastomer according to claim 3 or 4, characterized in that: The end-capping agent is: Any of .

6. The method for preparing a polyamide elastomer according to any one of claims 3 to 5, characterized in that: The catalyst is selected from: any one of triphenyl phosphite, phosphorous acid, sodium hypophosphite, sodium phosphite, trimethylchlorosilane, triethylsilicon chloride, tin chloride, stannous octoate, heteropoly acid unilateral chromium, heteropoly acid unilateral iron, heteropoly acid unilateral manganese, heteropoly acid unilateral aluminum, N,N'-dicyclohexylcarbodiimide, benzotriazole-N,N,N',N'-tetramethyluronium hexafluorophosphate or 1-hydroxybenzotriazole.

7. The method for preparing a polyamide elastomer according to any one of claims 3 to 6, characterized in that: The preparation method of the polyamide elastomer comprises the following steps: 24.2-121 parts of biphenyl dicarboxylic acid monomer, 108-194.4 parts of naphthalene dicarboxylic acid monomer, 30-208.8 parts of aliphatic diamine, 40-1000 parts of polyether amine, 0.1-40 parts of catalyst and 10-500 parts of deionized water are added to a reaction kettle respectively, and the mixture is heated to 50-100° C. under a nitrogen atmosphere and stirred for reaction for 0.5-1h, and the pH value of the solution is controlled at 7.5-8.5; then, the reaction kettle is sealed and heated, and the temperature is raised to 210-230° C. in the first stage for reaction for 1-3h; then the temperature is raised to 231-250° C. for reaction for 1-3h; h, venting 1 to 3 times in the middle; then raising the temperature of the reactor to 251 to 280°C, maintaining the vacuum degree at -0.08 to -0.095 MPa, continuing the reaction for 2 to 6 hours, and using negative pressure to suck 0.1 to 20 parts of the end-capping agent into the reactor, and continue the reaction for 0.5 to 2 hours, stop the polymerization reaction, introduce nitrogen into the reactor until it returns to normal pressure, open the reactor discharge bottom valve, continue to use 0.02-0.1 MPa nitrogen to extrude the material in the reactor from the discharge valve to the feed port of the twin-screw extruder, and vent, extrude, pelletize and dry to obtain the polyamide elastomer resin.

8. The method for preparing a polyamide elastomer according to claim 7, characterized in that: In the preparation method, the process conditions of the twin-screw extruder are as follows: The screw speed is controlled at 80-300rpm, the feeding rate is 3-40, and the temperature of each section of the extruder is: section 1: 220-260℃, section 2: 220-260℃, section 3: 220-260℃, section 4: 220-260℃, section 5: 271-290℃, section 6: 271-290℃, section 7: 271-290℃, section 8: 271-290℃, section 9: 271-290℃, section 10: 271-290℃, section 11: 271-290℃, section 12: 271-290℃, section 13: 271-290℃, section 14: 280-290℃.

9. A polyamide elastomer used as a compatibilizer, an active additive, a soft plastic or a coating material, wherein the polyamide elastomer is the polyamide elastomer according to claim 1 or 2, or is a polyamide elastomer prepared by the preparation method according to any one of claims 3 to 8.

10. The polyamide elastomer according to claim 9 is used as a compatibilizer, an active additive, a soft plastic or a coating material, characterized in that: The polyamide elastomer is used as an interface compatibilizer between inert resin and metal; or: The polyamide elastomer is used as a protective coating.

Citation Information

Patent Citations

  • High-toughness semi-aromatic polyamide resin and preparation method thereof

    CN113429565A

  • Environment-friendly ether-containing elastomer and preparation method thereof

    CN114349953A

  • Polyamide material, polyamide composite rubber sealing element and preparation method of polyamide composite rubber sealing element

    CN116199878A

  • Imide type catalytic promoter, polyimide film and preparation method

    CN118063491A

  • Polyamide block copolymer, preparation method, application and plastic product

    CN118684879A